Efficiency analysis in electricity transmission utilities (2009)
n those countries where the electric production chain has been disintegrated, transportation utilities (transmission as well as distribution) are subject to regulation or are under supervised activity. Regulation of activities considered as natural monopolies in network economies requires knowing or assessing efficient capital and operating expenditures (CAPEX and OPEX) depending on the output levels. The problem of determining the tariffs that transmission utilities can charge is tightly related to efficient OPEX levels. This work discusses the use of Data Envelopment Analysis and Stochastic Frontier Analysis to determine efficient frontiers for the electricity transmission activity. The results include relative efficiency and productivity indexes, as well as benchmarking peers. This information can be useful to the regulator to foster efficient performance of transmission utilities.